Chemically doped perylene diimide lamellae based field effect transistor with low operating voltage and high charge carrier mobility - Arulkashmir, Arulraj; Jain, Bhanprakash; John, Jino C.; Roy, Kanak; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Chemical doping of an electron transporter results in the formation of a radical anion containing semiconductor which showed high electron mobility (13 cm(2) V-1 s(-1)) at low operating voltage (1 V).

Approach to modulate the sensing range of molecular transducers - Jain, Bhanprakash; Dharmapurikar, Satej S. (Sensors and Actuators B-Chemical, 2015)
Transduction occurs upon binding of an analyte with a transducer. Specific binding involves the design and synthesis of receptors that is non trivial. Indeed, the task of designing a receptor for the smallest anion fluoride is very challenging. Herein, we take advantage of the basicity of fluoride ions that has affinity toward acidic proton. A commercially available 6-bromoisatin can sense fluoride ion in the concentration range of 0.5-3.9 ppm. Although the sensor is reaction based, the response is rapid. To further increase the linear range, dibromoisoindigo was synthesized. The linear range of this transducer was found to be between 0.5 ppm and 10.4 ppm. The transducer can be regenerated by adding proton source such as trifluoroacetic acid. Thus, transducers with variable sensing range have been designed and synthesized using acid base interaction. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Acidic proton; Basicity; Fluoride ion; Reversible sensor; Transducers

Phenols from green tea as a dual functional coating to prepare devices for energy storage and molecular separation - Das, Chayanika; Jain, Bhanprakash; Krishnamoorthy, Kothandam (Chemical Communications, 2015)
Polyphenols from green tea were used to electrolessly deposit gold on silk cocoons (SCs) and nanoporous aluminum oxide (AAO) templates. The gold coated cocoons were used as electrodes in supercapacitors and showed a capacitance as high as 254 F g(-1) and a specific power of 2287 W kg(-1). A metal coated AAO template was used for molecular separation.

Fluorescent carbon nanodots for targeted in vitro cancer cell imaging - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Niryikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2016)
Carbon quantum dots (CQDs or C-dots, <= 10nm in size) are tiny carbon nanoparticles being envisaged in biosensing, bio-imaging and biomolecular/drug delivery. In the present investigation, green fluorescent carbon quantum/nano dots (GCQDs, similar to 3 nm in size) were synthesized through facile chemical slicing method. Further, folic acid (FA) functionalized GCQDs (GCQDs-FA) were obtained to enhance their targeting ability. FA is known to positively influence the binding potential and penetration into the cancer cells because of high abundance of folate receptors (FR) on various cancer cell membranes. We report high biocompatibility, photoluminescence stability and excellent in vitro cancer cell cytoplasm and nucleus targeting performance of GCQDs-FA on MCF-7 breast cancer cells. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cancer cell bio-imaging; Carbon quantum/nano dots; Cell cytoplasm and nucleus targeting; Green fluorescence; Photoluminescence stability; Targeting ability

Fluorescent carbon nanodots for targeted in vitro cancer cell imaging (vol 4, pg 71, 2016) - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Nirvikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2019)

Instabilities as the origin of large-area self-assembled and aligned organic semiconductor nanocrystals - Venugopalan, Vijay; Jain, Bhanprakash; Mahale, Rajashree Y.; Subramani, Kumar; Krishnamoorthy, Kothandam (ACS Applied Electronic Materials, 2022)
Aligned nanocrystals of organic semiconductors (OSCs) are highly desirable for electronic devices and biomedical and photonic applications. Solution-based wet processing routes have the potential to produce aligned nanocrystals over large areas in small time frames. Herein, we demonstrate that by optimizing the hydrodynamic evaporative processes, controlled long-range crystalline assemblies of OSCs can be achieved (longest nanocrystal similar to 3 mm) purely through physical processes: namely, from fingering instabilities. Self-assembly is achieved here without strong noncovalent interactions such as hydrogen-bonding interactions. Experimentally our approach involves just placing a drop of a solution on an inclined substrate. Nanocrystals with widths of 300-800 nm and lengths of millimeters (length/width aspect ratios >10(5)) are formed in less than 2-8 s. A hydrazine chemiresistive sensor based on the aligned crystalline patterns show unprecedented responsivity (similar to 10(-6)), 2 orders greater than those of stick-slip patterns. Finally, experimental parameters that need optimization to achieve nanocrystal patterns are investigated in detail and pointers to fabricate such OSC nanocrystals are provided.
Keywords: aligned fibers; diketopyrrolopyrrole; fingering instability; nanocrystal arrays; naphthalenediimide; organic semiconductors